2009
DOI: 10.1111/j.1530-0277.2009.01069.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, Cocaine, and Brain Stimulation‐Reward in C57Bl6/J and DBA2/J Mice

Abstract: Background Pleasure and reward are critical features of alcohol drinking that are difficult to measure in animal studies. Intracranial self-stimulation (ICSS) is a behavioral method for studying the effects of drugs directly on the neural circuitry that underlies brain reward. These experiments had 2 objectives: first, to establish the effects of alcohol on ICSS responding in the C57Bl6/J (C57) and DBA2/J (DBA) mouse strains; and second, to compare these effects to those of the psychostimulant cocaine. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
53
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 74 publications
16
53
0
Order By: Relevance
“…C57BL/6 (Cazala et al, 1974). More recent comparisons of C57BL/6J and DBA/2J mice using hybrid frequency-rate procedures found no strain differences in ICSS thresholds, although maximal ICSS rates were greater in C57BL/6 mice (Elmer et al, 2010;Fish et al, 2010). In rats responding under a frequencyrate procedure, ICSS thresholds did not differ between Lewis, Fischer 344, and Sprague-Dawley rats, and in this study, maximal response rates also did not differ across strain (Lepore et al, 1996).…”
Section: A Statesmentioning
confidence: 52%
See 2 more Smart Citations
“…C57BL/6 (Cazala et al, 1974). More recent comparisons of C57BL/6J and DBA/2J mice using hybrid frequency-rate procedures found no strain differences in ICSS thresholds, although maximal ICSS rates were greater in C57BL/6 mice (Elmer et al, 2010;Fish et al, 2010). In rats responding under a frequencyrate procedure, ICSS thresholds did not differ between Lewis, Fischer 344, and Sprague-Dawley rats, and in this study, maximal response rates also did not differ across strain (Lepore et al, 1996).…”
Section: A Statesmentioning
confidence: 52%
“…Effects of ethanol were examined in C57BL/6J and DBA/2J mice using a hybrid frequency-rate procedure. Administration of ethanol resulted in ICSS facilitation in each strain and did so across a broader range of doses and pretreatment times in DBA/2J mice compared with C57BL/6J mice (Fish et al, 2010). The ability of ethanol to facilitate ICSS in Abuse Potential Testing ICSS in C57BL/6J mice is consistent with its ability to maintain self-administration in this strain, but the effect in DBA/2J mice is inconsistent with data showing that ethanol does not maintain self-administration in this strain (Risinger et al, 1998).…”
Section: A Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…ICSS was performed as detailed previously (54). Briefly, mice (26 WT and 27 Ube3a m-/p+ mice) were anesthetized (120 mg/kg ketamine, 9 mg/kg xylazine; Hospira), and 0.25% bupivacaine (Hospira) was applied to the scalp incision site.…”
Section: Methodsmentioning
confidence: 99%
“…Both strains had similar BSR thresholds (Elmer et al, 2010;Fish et al, 2010) and no strain difference was found in amphetamine potency (Elmer et al, 2010); however, DBA mice were more sensitive to the threshold lowering effects of cocaine (Fish et al, 2010). Additionally, the two strains were differentially sensitive to morphine and alcohol.…”
Section: Introductionmentioning
confidence: 83%